Some Variants of Krasnoselskii-Type Fixed Point Results for Equiexpansive Mappings with Applications. (11th September 2021) - Ahmad, Niaz; Mehmood, Nayyar; Al-Rawashdeh, Ahmed
Abstract : In this paper, we investigate the Krasnoselskii-type fixed point results for the operator F of two variables by assuming that the family F x, . : x is equiexpansive. The results may be considered as variants of the Krasnoselskii fixed point theorem in a general setting. We use our main results to obtain the existence of solutions of a fractional evolution differential equation. An example of a controlled system is given to illustrate the application.